2018
DOI: 10.1002/cncr.31566
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of mailed reminders with and without fecal immunochemical tests for Medicaid beneficiaries at a large county health department: A randomized controlled trial

Abstract: A health department-based, mailed FIT program targeting Medicaid beneficiaries was feasible. Including a FIT kit resulted in greater screening completion than a reminder letter alone. Further research is needed to understand the comparative cost-effectiveness of these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 25 publications
(52 reference statements)
2
37
1
Order By: Relevance
“…The FIT return rates achieved in the current study were similar to those achieved in some clinic‐based studies of mailed FIT outreach, suggesting that health plan–based, mailed FIT programs can be as effective as programs initiated by individual clinics or health centers. The current study findings also are approximately consistent with those of a previous investigation of a CRC screening intervention by Medicaid health plans, in which Brenner et al reported a return rate of 21% for a centralized FIT program for Medicaid enrollees that first removed those enrollees who had an invalid address (19%) or self‐reported recent screening (11%) . The findings of the current study demonstrated completion rates to be particularly high in Health Plan Washington among enrollees who were due for and answered the live reminder telephone call (76.2%); these findings were consistent with previous research indicating that tailored telephone outreach can significantly increase rates of CRC screening .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The FIT return rates achieved in the current study were similar to those achieved in some clinic‐based studies of mailed FIT outreach, suggesting that health plan–based, mailed FIT programs can be as effective as programs initiated by individual clinics or health centers. The current study findings also are approximately consistent with those of a previous investigation of a CRC screening intervention by Medicaid health plans, in which Brenner et al reported a return rate of 21% for a centralized FIT program for Medicaid enrollees that first removed those enrollees who had an invalid address (19%) or self‐reported recent screening (11%) . The findings of the current study demonstrated completion rates to be particularly high in Health Plan Washington among enrollees who were due for and answered the live reminder telephone call (76.2%); these findings were consistent with previous research indicating that tailored telephone outreach can significantly increase rates of CRC screening .…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the current study data from Health Plan Oregon have suggested lower than expected numbers of invalid addresses; only 83 of 3449 addresses (2.4%) initially were determined to be invalid based on US Postal Service records and an additional 157 of 2812 addresses (5.6%) were removed after the introductory letter was mailed. In contrast, Brenner et al reported a 19% rate of invalid addresses among Medicaid enrollees in North Carolina . More research is needed to understand and address these and other implementation challenges.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This nding that more comprehensive efforts yielded higher screening rates supports prior research suggesting that FIT return rates can be increased by delivering more and additional types of reminders. [29][30][31] The con gurational analyses identi ed multiple ways for health systems to achieve higher rates of screening. It found size to be an important contextual factor, with different solutions for larger health systems than those for smaller health systems.…”
Section: Discussionmentioning
confidence: 99%